2013
DOI: 10.1007/s10499-013-9707-9
|View full text |Cite
|
Sign up to set email alerts
|

Food selection of burbot (Lota lota L.) larvae reared in illuminated net cages in mesotrophic Lake Maróz (north-eastern Poland)

Abstract: Feeding and food selection of burbot (Lota lota L.) larvae reared in illuminated cages were studied. The experiment was carried out in mesotrophic Lake Maróz, in northeastern Poland, for 6 weeks in two successive years. The initial stocking density was 1,250 larvae (20 DPH) per cage. Food selection according to the zooplankton groups (Rotifera, Cladocera and Copepoda) and length classes was expressed by the Strauss linear selectivity index (L). Zooplankton species composition in the lake was similar in the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Feeding and foraging successfully during the larval stage is critical to fish survival (Devries et al, 1998;Skrzypczak et al, 1998). Many factors affect the success of larval predation, including the ability of the predator to consume its prey, morphological constraints during ontogeny, and prey size and abundance (Furgała-Selezniow et al, 2014). It has been reported that fish larvae are gap-limited predators, and they usually swallow prey whole when foraging.…”
Section: Introductionmentioning
confidence: 99%
“…Feeding and foraging successfully during the larval stage is critical to fish survival (Devries et al, 1998;Skrzypczak et al, 1998). Many factors affect the success of larval predation, including the ability of the predator to consume its prey, morphological constraints during ontogeny, and prey size and abundance (Furgała-Selezniow et al, 2014). It has been reported that fish larvae are gap-limited predators, and they usually swallow prey whole when foraging.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional method to analyze the feeding characteristics of organisms is to identify the gut contents via the naked eye or with a microscope (Chang et al, 2011;Furgała-Selezniow et al, 2014). However, these methods have limited results because they can be derived from the decomposition of feeding sources remaining in the gut.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, seasonal periods of its maximum migratory activity for adults have been established [1]. In some countries, this species is included in the Red Data Book of ichthyofauna [5].…”
Section: Introductionmentioning
confidence: 99%